The Donigers of Great Neck : A Mythologized Memoir - Doniger, Wendy (Book collections on Project MUSE., 2019)
"This is the story of the contrasting Judaisms that Wendy Doniger's two parents brought from their very different homes in Europe during World War I; of their paths to a shared but sharply bifurcated life in America during World War II, her father a publisher, her mother a political activist; and of the ways in which their attitudes to religion in general, and Judaism in particular, influenced the author's development as a Jewish woman and a scholar of religion"--